Histopathological Correlations of Qualitative and Quantitative Temporopolar MRI Analyses in Patients With Hippocampal Sclerosis - Zaidan, Bruna Cunha; Cardoso, Ingrid Carolina da Silva; Campos, Brunno Machado de; Silva, Luciana Ramalho Pimentel da; Coelho, Vanessa C. Mendes; Silveira, Kairo Alexandre Alves; Amorim, Bárbara Juarez; Alvim, Marina Koutsodontis Machado; Tedeschi, Helder; Yasuda, Clarissa Lin; Ghizoni, Enrico; Cendes, Fernando; et al. (Frontiers in Neurology, 2021)
Hippocampal sclerosis (HS) is a common cause of pharmacoresistant focal epilepsy. Here, we (1) performed a histological approach to the anterior temporal pole of patients with HS to evaluate cortical and white matter (WM) cell populations, alteration of myelin integrity and markers of neuronal activity, and (2) correlated microscopic data with magnetic resonance imaging (MRI) findings. Our aim was to contribute with the understanding of neuroimaging and pathophysiological mechanisms of temporal lobe epilepsy (TLE) associated with HS. We examined MRIs and surgical specimens from the anterior temporal pole from TLE-HS patients (n = 9) and compared them with 10 autopsy controls. MRIs from healthy volunteers (n = 13) were used as neuroimaging controls. Histological techniques were performed to assess oligodendrocytes, heterotopic neurons, cellular proliferative index, and myeloarchitecture integrity of the WM, as well as markers of acute (c-fos) and chronic (ΔFosB) activities of neocortical neurons. Microscopic data were compared with neuroimaging findings, including T2-weighted/FLAIR MRI temporopolar blurring and values of fractional anisotropy (FA) from diffusion-weighed imaging (DWI). We found a significant increase in WM oligodendrocyte number, both in hematoxylin and eosin, and in Olig2-stained sections. The frequencies of oligodendrocytes in perivascular spaces and around heterotopic neurons were significantly higher in patients with TLE–HS compared with controls. The percentage of 2',3'-cyclic-nucleotide 3'-phosphodiesterase (CNPase; a marker of myeloarchitecture integrity) immunopositive area in the WM was significantly higher in TLE-HS, as well as the numbers of c-fos- and ΔFosB-immunostained neocortical neurons. Additionally, we demonstrated a decrease in axonal bundle integrity on neuroimaging, with a significant reduction in the FA in the anterior temporal pole. No differences were detected between individuals with and without temporopolar blurring on visual MRI analysis, considering the number of oligodendroglial cells and percentage of WM CNPase-positive areas. Also, there was no relationship between T2 relaxometry and oligodendrocyte count. In conclusion, our histopathological data support the following: (1) the hypothesis that repetitive neocortical neuronal activity could induce changes in the WM cellular constitution and myelin remodeling in the anterior temporal pole from patients with TLE-HS, (2) that oligodendroglial hyperplasia is not related to temporal blurring or T2 signal intensity on MRI, and (3) that reduced FA is a marker of increase in Olig2-immunopositive cells in superficial temporopolar WM from patients with TLE-HS.